(untitled) - Kondo, Dorinne K. (Chicago, 1990)
The ethnography of Japan is currently being reshaped by a new generation of Japanologists, and the present work certainly deserves a place in this body of literature. . . . The combination of utility with beauty makes Kondo's book required reading, for those with an interest not only in Japan but also in reflexive anthropology, women's studies, field methods, the anthropology of work, social psychology, Asian Americans, and even modern literature.
Keywords: Women,Women,Women,Group identity,Self-perception; Employment,Social conditions,Economic conditions; Japan,Japan,Japan,Japan,Japan